Amino acid-functionalized heteropolyacids as efficient and recyclable catalysts for esterification of palmitic acid to biodiesel. (1st February 2016) - Han, Xiao-Xiang; Chen, Ke-Ke; Yan, Wei; Hung, Chin-Te; Liu, Li-Li; Wu, Pei-Hao; Lin, Kai-Chen; Liu, Shang-Bin
Graphical abstract: Amino acid-functionalized heteropolyacid catalysts show superior activity, durability, and unique self-separation property desirable for facile recovery and recycling for conversion of free fatty acids to biodiesel. Highlights: Amino acid-grafted heteropolyacids show high activity for conversion of fatty acid. Organic salt catalysts show strong acidity desirable for esterification reaction. Catalyst system shows self-separation property favorable for separation/recycling. Abstract: The organic–inorganic hybrid catalysts, namely [GlyH] x H3− x PW12 O40 ( x = 1.0–3.0), prepared by mixing varied amounts of glycine (Gly) and tungstophosphoric acid (TPA), were characterized by different analytical and spectroscopic techniques such as TGA, XRD, FT-IR, and 1 H and 13 C NMR. In particular, their acidic properties were probed by solid-state 31 P MAS NMR of adsorbed trimethylphosphine oxide. The catalytic performances of various Gly–TPA catalysts during esterification reaction of palmitic acid with methanol for production of methyl palmitate were illustrated and examined. The catalyst system revealed self-separation characteristics, forming biphasic product/catalyst layers to render facile product separation and catalyst recycling. The [GlyH]1.0 H2.0 PW12 O40 catalyst was found to exhibit the best activity with an optimal biodiesel yield of 93.3%.